Carbon futures and clean energy stocks: Do they hedge or safe haven against the climate policy uncertainty? - Mohammad Enamul Hoque; Sourav Batabyal (Journal of Risk and Financial Management, 2022)
Using the GARCH model and quantile regression with dummy variables, we investigate the hedging and safe haven properties of carbon futures and clean energy stocks against the U.S. climate policy uncertainty (CPU). We discover that carbon futures and clean energy stocks have a weak hedge and a semi-strong safe haven in different market conditions. Carbon futures exhibit a strong safe haven in both bull and bear markets, depending on the degree of uncertainty. Clean energy stocks, on the other hand, possess a weak hedge across market conditions and a strong safe haven in bull markets. Sub-sample analyses of prior- and post-Paris Agreement of 2016 also exhibit consistent results for safe haven properties of carbon futures and clean energy stocks.
Keywords: 650; quantile regression; carbon futures; clean energy stocks; climate policy uncertainty; GARCH model; hedge; safe haven